The Status of Dividend Debts as a Basis for Determining Bankruptcy - Andreas Marlas Raja Pardamean Lumban Gaol; Ubaidillah Kamal (Universitas Negeri Semarang, 2026)
Developments in legal relationships within the corporate world indicate that obligations are no longer limited to contractual relationships alone, but also arise from internal corporate mechanisms, one of which is the distribution of dividends. In practice, issues arise when dividends that have been approved but not yet paid are used as the basis for a bankruptcy petition, leading to a debate over whether dividends can be classified as debt under bankruptcy law. This study aims to analyze the status of dividends as debt under Indonesian bankruptcy law and their relationship to the principle of simplified proof. The research method employed is a normative legal approach using both statutory and case-law analyses, through an examination of the Limited Liability Companies Act, the Bankruptcy Act, and the PKPU, as well as relevant court rulings. The research findings indicate that dividends decided upon by the General Meeting of Shareholders (GMS) and that have become due substantively meet the elements of a debt because they possess economic value, arise from a contractual obligation, are binding, and are enforceable. However, in practice, the application of this concept is not divorced from the principle of simple proof, which is a characteristic of bankruptcy law. If there is a dispute regarding the validity of the GMS, the amount of dividends, or the company’s financial condition that requires complex proof, then filing for bankruptcy becomes inappropriate. Thus, although dividends can be categorized as debt substantively, their use as the basis for a bankruptcy petition must be strictly limited. This restriction is important to prevent the misuse of bankruptcy as a tool for coercion in corporate disputes, as well as to maintain legal certainty, justice, and business continuity, and to ensure balanced protection for creditors and shareholders.